Quality and Creativity of Teachers through Teacher Education - Adhikari, T. N. (Pragya Darshan प्रज्ञा दर्शन, 2024)
In order to foster the excellence and originality of teachers, this article attempts to highlight some of the ideas that are essential for teacher education programmes and for instructors themselves. The core skeleton of any nation should be its teachers. Physical strength between vertebrate animals and non-vertebrate animals is well established. In the same manner, a community cannot effectively thrive without teachers of high calibre. Effective community development indicates a country's development in a wealthy manner. Today's instructors must consider their professional growth as part of their teacher education, just as a nation must manage in order to develop. Our early teachers changed basic existence into the state it is in today. Teachers should become very confident in their ability to instruct. The aim of teacher education ought to be to prepare teachers who are capable and innovative in their instruction. The profession of teaching is one that needs to be widely accepted. In the past, a teacher was like a spiritual person, and that quality should still exist now in order to impart knowledge to pupils and prepare them to influence the direction of a nation's development. In such cases, teacher education should be designed to support teachers' professional growth in terms of enhancing their critical thinking abilities. The kids will acquire the right knowledge if the teacher is flawless in every way. Teacher preparation shouldn't be seen as just a means of landing a job; rather, it should be viewed in the context of a teacher's role as a source of truth as well as the philosophy of the cosmos and nature. Only a top-notch instructor can present the information. Professional growth and inventiveness are required qualities for this capacity. The author's experience and document analysis form the foundation of the study's methodology.